2010
DOI: 10.1111/j.1528-1167.2010.02572.x
|View full text |Cite
|
Sign up to set email alerts
|

Small temporal pole encephaloceles: A treatable cause of “lesion negative” temporal lobe epilepsy

Abstract: Summary Epilepsy due to encephaloceles of the temporal pole may be an under recognized, treatable cause of refractory temporal lobe epilepsy (TLE). We describe three adult patients initially labeled “lesion negative” TLE. In all, video–electroencephalography (EEG) revealed ictal theta in the left temporal region and positron emission tomography (PET) showed temporal lobe hypometabolism, but neuropsychology revealed preserved verbal memory. Close inspection of structural magnetic resonance imaging (MRI) suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 6 publications
6
67
0
1
Order By: Relevance
“…In light of these findings, there are major arguments to think that STPE in patients with TLE are not coincidental. The fact that several patients in our series, as well as in others, [5][6][7][8][9]13,14 were rendered seizure-free after a small resection that included the herniated parenchyma, suggests a significant participation of this type of lesion in the epileptogenic zone. Moreover, in patients with RFE, ictal EEG showed a pattern congruent with the localization of the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In light of these findings, there are major arguments to think that STPE in patients with TLE are not coincidental. The fact that several patients in our series, as well as in others, [5][6][7][8][9]13,14 were rendered seizure-free after a small resection that included the herniated parenchyma, suggests a significant participation of this type of lesion in the epileptogenic zone. Moreover, in patients with RFE, ictal EEG showed a pattern congruent with the localization of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, evaluation of ictal nonverbal reaction to sensory stimuli and assessment of the patient's ability to recall ictal events postictally (such us the inability to speak and comprehend during the seizure) would be more appropriate to determine ictal awareness and avoid classifying an aphasic seizure as a CPS. 32,35 Although several of our cases show that medically refractory epilepsy associated with STPE may be remediable by surgery, the optimal surgical strategy is still controversial, [5][6][7][8][9]13 since the epileptogenic zone in these cases may not necessarily overlap perfectly with the radiologic alteration depicted on MRI. Moreover, we and others 13 have shown that STPE can be clearly bilateral in some patients, raising the concern that there could be patients with bilateral pathology despite just having a unilateral lesion on the MRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chassoux et al [12] and Abou-Hamden et al [13] found that histopathologically MRI- TLE resulted from microencephalocele or focal cortical dysplasia in the temporal lobe. Carne et al [2] demonstrated that the extent of hypometabolism of MRI- TLE is broader than HS + TLE, suggesting that they are distinct from each other.…”
Section: Discussionmentioning
confidence: 99%